The influence of a special technique for developing coordination abilities on the level of technical preparedness and development of psycho-physiological functions of young volleyball players 14-16 years of age - Kosina, Z.; Goloborodko, Y.; Boichuk, Y.; Sobko, I.; Repko, O.; Bazilyuk, T.; Prokopenko, Ir.; Prokopenko, Iv.; Prokopenko, A.; Tararaka, N.; Osiptsov, A.; Kostiukevych, V.; et al. (Journal of Physical Education and Sport, 2018)
Purpose: development and experimental verification of the technique of using the coordination (high-speed) ladder to improve the technical skills and psychophysiological functions of young volleyball players. Material and methods.Participants: 24 volleyball players from the Municipal Institution "Complex Children's and Youth Sports School No. 8 (14-16 years); 12 athletes entered the control group, 12 in the experimental group. The experiment was conducted during 3 month in the preparatory period at the stage of basic training of the third year of training. The experimental group trained with a coordinating ladder. At the beginning and at the end of the experiment, psychophysiological testing was conducted. The following tests were used: the parameters of a simple and complex reaction in various modes of signal feeding, indicators of efficiency and the nervous system were determined. Intergroup and intra-group differences in the tests were determined. Results.The construction of a training and training process in volleyball with the use of a coordination ladder with a rapid change in the type of activity had a positive effect on the psychophysiological state of volleyball players. At the representatives of the experimental group in the test "The response of choice, the number of errors" the result significantly improved (p<0.001). After the experiment, the control and experimental groups began to differ reliably among themselves. Similar data were obtained in the tests "Response time of choice in the feedback mode" and "Mental stability according to the Schulte test". The obtained data testify to the advisability of using a coordination ladder with the subsequent performance of another kind of activity as an attacking blow and receiving the ball from the bottom in the training of young volleyball players to optimize the psychophysiological state. Conclusions.The method of application of the coordination (high-speed) ladder is developed. The technique is an effective, accessible and reliable means of improving the psychophysiological state, increasing the physical and technical preparedness of young volleyball players.